2021
DOI: 10.3390/su13020964
|View full text |Cite
|
Sign up to set email alerts
|

Re-Visiting Design Thinking for Learning and Practice: Critical Pedagogy, Conative Empathy

Abstract: This paper argues for the importance of design thinking as a creative, collaborative activity to equip students, instructors, and practitioners with important skills to address “wicked problems” that are transforming tourism and hospitality in a (post-)COVID-19 Anthropocene. Design Thinking (DT) and Design Thinking for Engaged Learning (DTEL) are becoming increasingly popular to incorporate in practice and in courses offered across various fields of study, including tourism and hospitality. The paper reviews s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
2
24
0
2
Order By: Relevance
“…The inclusion of metacognition in design tasks is well supported by a myriad of authors [5,7,56,59,60], but as they have reported, several cognitive pitfalls can occur, especially for unwary designers, if internal thought processes are not well understood and used [60]. The shortcomings or failures have been seen as a result of top-down processing, which can lead to encoding failures, inattentional blindness, confirmation bias, cognitive fixation, among other things [60].…”
Section: Self-directed Learning and Design Thinkingmentioning
confidence: 99%
See 4 more Smart Citations
“…The inclusion of metacognition in design tasks is well supported by a myriad of authors [5,7,56,59,60], but as they have reported, several cognitive pitfalls can occur, especially for unwary designers, if internal thought processes are not well understood and used [60]. The shortcomings or failures have been seen as a result of top-down processing, which can lead to encoding failures, inattentional blindness, confirmation bias, cognitive fixation, among other things [60].…”
Section: Self-directed Learning and Design Thinkingmentioning
confidence: 99%
“…Employing different stakeholders or the content of different disciplines in design tasks can result in new knowledge and skills, especially creativity, innovativeness, digital skills, interpersonal skills, and creative self-efficacy and design flow experience [53,54]. Design thinking shows values such as practicality, ingenuity, empathy, and appropriateness as well as values rooted in humanity, e.g., subjectivity, imagination, commitment, and justice [55,56], as human-centred design is socially situated in values and sense making [56,57]. Moreover, it was argued by [7,56] that design thinking can make a change towards SDGs and sustainable architecture, and it may provoke the use of different strategies and methods as a part of self-directed learning to develop innovativeness, creativity and digital skills.…”
Section: Self-directed Learning and Design Thinkingmentioning
confidence: 99%
See 3 more Smart Citations